2014
DOI: 10.1111/eos.12157
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 contributes to capsaicin‐induced facial cold hyperalgesia in rats

Abstract: Orofacial cold hyperalgesia is known to cause severe persistent pain in the face following trigeminal nerve injury or inflammation, and transient receptor potential (TRP) vanilloid 1 (TRPV1) and TRP ankylin 1 (TRPA1) are thought to be involved in cold hyperalgesia. However, how these two receptors are involved in cold hyperalgesia is not fully understood. To clarify the mechanisms underlying facial cold hyperalgesia, nocifensive behaviors to cold stimulation, the expression of TRPV1 and TRPA1 in trigeminal gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…TRPV1 is commonly recognized as a main noxious heat sensor, being involved in thermal hyperalgesia [22,23,45], inflammatory pain [46], notably facial pain [47,48]. Our study suggests that TRPV1 could also be involved in mechanical and cold hypersensitivity during NP as shown for facial pain [47,48], yet its role appears shorter lasting than in heat hyperalgesia. The TRPV1 antagonist SB366791 dose-dependently alleviated heat and mechanical sensitivity in the model of chronic constriction injury of the sciatic nerve in mice when injected into the injured paw [49].…”
Section: Trpv1 In Neuropathic Painsupporting
confidence: 50%
“…TRPV1 is commonly recognized as a main noxious heat sensor, being involved in thermal hyperalgesia [22,23,45], inflammatory pain [46], notably facial pain [47,48]. Our study suggests that TRPV1 could also be involved in mechanical and cold hypersensitivity during NP as shown for facial pain [47,48], yet its role appears shorter lasting than in heat hyperalgesia. The TRPV1 antagonist SB366791 dose-dependently alleviated heat and mechanical sensitivity in the model of chronic constriction injury of the sciatic nerve in mice when injected into the injured paw [49].…”
Section: Trpv1 In Neuropathic Painsupporting
confidence: 50%
“…Contrasting these findings, several recent rodent studies using, e.g., back-labeling of cutaneous afferents and unbiased single cell RNA sequencing have suggested that TRPA1 + nociceptors, which do not express TRPV1 are much more common than previously assumed 37,51,56,82,85 . As such the expressional patterns of TRP-channels in nociceptive DRG neurons and on peripheral nociceptors and in particular, the functional overlap between TRPA1 and V1 in the nociceptive system of rodents remain unknown.…”
Section: Introductionmentioning
confidence: 79%
“…Facial inflammation subsequently reduces the acidity in the inflamed site, which increases TRPV1 expression in nociceptors. TRPV1 activation facilitates the intracellular influx of Ca 2+ , which sensitizes TRPA1, leading to orofacial cold hypersensitivity [13].…”
Section: Local Pathological Changes Contribute To Nociceptive Neuronamentioning
confidence: 99%